Implementation of evidence-based assessment of upper extremity in stroke rehabilitation: From evidence to clinical practice - Margit Alt Murphy; Ann Björkdahl; Gunilla Forsberg-Wärleby; Carina U. Persson (Medical Journals Sweden, 2021)
Objective: There is an evidence-practice gap in assessment of the upper extremities during acute and subacute stroke rehabilitation. The aim of this study was to target this gap by describing and evaluating the implementation of, and adherence to, an evidence--based clinical practice guideline for occupational therapists and physiotherapists. Methods: The upper extremity assessment implementation process at Sahlgrenska University Hospital comprised 5 stages: mapping clinical practice, identifying evidence-based outcome measures, development of a guideline, implementation, and evaluation. A systematic theoretical framework was used to guide and facilitate the implementation process. A survey, answered by 44 clinicians (23 physiotherapists and 21 occupational therapists), was used for evaluation. Results: The guideline includes 6 primary standard-ized assessments (Shoulder Abduction, Finger Extension (SAFE), 2 items of the Actions Research Arm Test (ARAT-2), Fugl-Meyer Assessment of Upper Extremity (FMA-UE), Box and Block Test (BBT), 9-Hole Peg Test (9HPT), and grip strength (Jamar hand dynamometer)) per-formed at specified time-points post-stroke. More than 80% (35 to 42) clinicians reported reported being content with the guideline and the implementation process. Approximately 60-90% of the clinicians reported good adherence to specific assessments, and approximately 50% report-ed good adherence to the agreed time-points. Comprehensive scales were more difficult to implement compared with the shorter screening scales. High levels of work rotation among staff, and the need to prioritize other assessments during the first week after stroke, hindered to implementation. Conclusion: The robustness of evidence, adequate support and receptive context facilitated the implementation process. The guideline enables a more structured, knowledge-based and consistent assessment, and thereby supports clinical decision-making and patient involvement.